Biological approaches to spinal disc repair and regeneration for clinicians - Härtl, Roger; Bonassar, Lawrence J. (Thieme, 2017)
Although there have been significant advancements in minimally invasive spinal surgery techniques in the last few decades, optimal outcomes for chronic low back pain remain elusive. A number of promising clinical trials have been conducted using tissue engineering and biological interventions for disc degeneration. Written by renowned innovators, this is the first book that covers implementation of these groundbreaking approaches for disc disease. The text begins with key fundamentals including anatomy and physiology, pathophysiology, imaging and biomechanics to delineate healthy versus diseas.